2022
DOI: 10.5772/intechopen.95270
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-Specific Pair Bonding in Gibbons (Hylobatidae)

Abstract: This study provides the first statistically significant evidence that the mechanisms of how pair bonds are created or maintained differ between gibbon taxa. We examine the pair bond in captive pairs of three genera of gibbons (Hylobatidae): siamangs (Symphalangus, N = 17 pairs), crested gibbons (Nomascus, N = 7 pairs), and pileated gibbons (Hylobates pileatus, N = 9 pairs). In the first part of this study, we determine three generally-accepted indicators of pair-bond strength (mutual grooming, behavioral synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For instance, siamang fathers are often involved in allomaternal care by carrying infants during their second year of life (Alberts 1987 ; Chivers 1974 ; Lappan 2008 ). Additionally, siamangs appear to have more cohesive groups than white-handed gibbons and pileated gibbons ( H. pileatus ) (Chivers 1976 ; Geissmann et al 2020 ; Palombit 1996 ), and may even have a stronger pair-bond than other gibbon species (Geissmann et al 2020 ). Munir ( 2018 ) reported siamangs’ success and high potential in cognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, siamang fathers are often involved in allomaternal care by carrying infants during their second year of life (Alberts 1987 ; Chivers 1974 ; Lappan 2008 ). Additionally, siamangs appear to have more cohesive groups than white-handed gibbons and pileated gibbons ( H. pileatus ) (Chivers 1976 ; Geissmann et al 2020 ; Palombit 1996 ), and may even have a stronger pair-bond than other gibbon species (Geissmann et al 2020 ). Munir ( 2018 ) reported siamangs’ success and high potential in cognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…Florkiewicz et al, 2018). One example of synchronous activity in gibbons includes vocal duetting, where songs strengthen social bonds and advertise territorial boundaries (Geissmann, 1993). However, this does not necessarily suggest that chimpanzees do not exhibit facial synchrony or that gibbons are unable to maintain multiple relationships with others.…”
Section: Discussionmentioning
confidence: 99%
“…While there is variability in the quality (B. Florkiewicz et al, 2018; Geissmann et al, 2020) and quantity (Barelli et al, 2013) of social relationships among gibbons, most live in relatively small social groups consisting of one set of pair-bonded individuals and their offspring (R. Palombit, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…While our results support male-biased investment in general, whether grooming is sex-biased or equal has been debated as many studies presented controversial results, even within Hylobatidae (reviewed in [ 18 ]). For instance, in wild H. lar , studies have found male-biased grooming in three pairs, female-biased grooming in two pairs and equal grooming in one pair [ 42 , 70 72 ], and the results are more complicated when including other genera in Hylobatidae or species in captivity [ 18 , 73 ]. This controversy might be because of the different social and reproductive contexts.…”
Section: Discussionmentioning
confidence: 99%